New generation cardioverter‐defibrillator lead with a floating atrial sensing dipole: Long‐term performance - Safak, Erdal; D´Ancona, Giuseppe; Kaplan, Hilmi; Caglayan, Evren; Kische, Stephan; Öner, Alper; Ince, Hüseyin; Ortak, Jasmin (Pacing and clinical electrophysiology, 2018)
Objectives The study aim is to present the long‐term performance of a new generation implantable cardioverter defibrillator (ICD) electrode with floating atrial dipole (Linox S DX, Biotronik, Berlin, Germany). Background The single ICD electrode with a floating dipole in the atrial chamber was introduced about 15 years ago to overcome risk of inappropriate shock. Methods After implantation, internal electrocardiogram data were prospectively collected via telemonitoring (Home Monitoring, Biotronik). Results A total of 93 patients (81.5% male, 18.5% female; 58.9 ± 12.3 years) were implanted with a single–chamber ICD using the Linox S DX. Patients were followed up for a median of 693 days (33–2,460 days). At time of implantation average p‐wave value was 3.5 ± 1.7 mV and remained stable throughout follow‐up with an average value of 3.7 ± 1 mV (P = 0.2). A total of 460 arrhythmic episodes were recorded and 185 (40.2%) were incorrectly stratified by the device software. Seven patients (7.5%) experienced inappropriate ICD therapy. In three patients, VT episodes were not detected and remained untreated. Conclusions Although the Linox S DX lead presents a satisfactory long‐term stability of the atrial sensing, many of the messages sent to the device during follow‐up were incorrectly classified by the ICD software. As a result, inappropriate therapy occurred with a rate similar to that observed with dual‐chamber ICDs, but some malignant arrhythmias remained undiagnosed and untreated while occurring. Results in larger prospective cohorts should be analyzed and software improvements of the device should be suggested to overcome these potential drawbacks.